A gameplan into the future a 5-year strategic plan for New Era Parts and Auto Supply - Que, Genesis M. (Davao City School of Management, University of the Philippines Mindanao, 2007)
For the past three years, New Era Parts and Auto Supply has been showing consistent growth in business despite strong market competition in the supply of automotive second hand and surplus spare parts in the Davao market. A niche player with less than 5% market share in the second hand spare parts category, the company was able to effectively carve a niche in the supply of second hand Japanese and Korean make automobile engines where only a few players cared to venture. Out of the more than 100 auto supply establishments in Davao City, less than 7% engaged in the supply of surplus and second hand automobile engines. Inspired by the prospects of initial growth, New Era Parts is assessing its strategy to sustain the current momentum and come up with a strategic plan that would serve as a blueprint to leapfrog the company?s market position in the next five years. This intent is being considered despite the challenges faced by company in accelerating the growth of the business due to its very limited resources vis-à-vis its high capitalization requirement. The study examines the internal strengths and weaknesses of the organization and identifies the opportunities and threats in its external environment. Using various managerial tools of analysis, the study was able to come up with strategic options that the company can pursue. These strategic options include several interrelated businesses where opportunities for growth is bright that can complement the existing operations of New Era Parts aimed at strengthening the company?s position in the supply chain either via vertical or horizontal integration. Additional funding for the proposed expansion will come from loan facility of commercial banks or government lending institutions, which the family is considering to avail of with the family?s property as collateral. Based on several strategic options which includes business expansion, service diversification, and product differentiation, the company was able to arrive at the most viable strategy by subjecting all of the options to the various analytical and decision-making tools. The result was the strategic consideration for the company to venture into multi business diversification as the most feasible option to sustain growth. This strategy got the highest qualitative score of 6.025. It allows the company to diversify into highly related businesses complementary to its current operations.
Thesis, Graduate(Master in Management)--University of the Philippines Mindanao, 2007
Keywords: Strategic plan